SOCIO-PEDAGOGICAL SUPPORT TO YOUTH PARTICIPATION IN INTEGRATION PROCESS - Pigozne, Tamara; Pigoznis, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The purpose of the article is on the basis of theoretical formulations to analyze participation and integration as pedagogical category and socio-pedagogical means, facilitating the participation of youth in integration process in two aspects – in educational system and labour market, linkages between participation and understanding the integration  as terminal (related to life goals), instrumental (means of reaching life goals) and opportune (related to opportunities) value as well as implicants of efficient participation.